A new calculation method of casing external squeezing loads in complex formation. Issue 5 (4th July 2016) - Yan, Keju; Guan, Zhichuan; Chen, Hao; Zhao, Xiaofeng; Zhang, Hongning
Abstract : Purpose: – Casing damage problems are increasingly prominent in oil fields, most of which were caused by casing external squeezing loads. The traditional calculation method of casing external squeezing loads is not very accurate now, especially in complex formation. The purpose of this paper is to propose a new calculation method to solve the problem of actual casing loads under above conditions. Design/methodology/approach: – Based on Lame's model of elastic mechanics, a new calculation method of casing external squeezing loads is deduced. Comprehensive influence laws of the loads which caused by in-situ stress, internal pressure, formation parameters, cement annulus parameters and casing parameters are analyzed. Findings: – The paper provides a new calculation method of casing external squeezing loads, by which the dispersion effect of internal liquid pressure caused by casing wall material is eliminated. The main influence factors of casing external squeezing loads are in-situ stress and formation elastic modulus. Research limitations/implications: – The model and boundary conditions used in the paper is based on elastic mechanics. The accuracy of the calculation results depends on the quality and accuracy of the input formation parameters. Originality/value: – This paper proposes a new method to calculate casing external squeezing loads. And compared with traditional methods, this method is more practical.